Association between atrial fibrillation, frailty, and geriatric syndromes in the late elderly in a south Belgian outpatient and inpatient setting - Christophe de Terwangne; Antonio Sorgente; Smarandita Macovei; Thibauld Preumont; Gianbattista Chierchia; Carlo de Asmundis; Antoine de Meester; Pierre Hanotier (American Heart Journal Plus, 2022)
Study objective: This study aims to analyze the relationship between AF, frailty, and geriatric syndromes in elderly patients in an outpatient and inpatient setting in a South Belgian hospital. Participants, design and setting: This is a single center case-control retrospective study including 207 patients enrolled from an outpatient and inpatient setting of the Department of Geriatrics, Jolimont Hospital Group. Frailty was assessed using a complete geriatric assessment and Rockwoods Clinical Frailty Scale. Results: AF was strongly associated with age, cardiovascular history, congestive heart failure, as well as with multiple geriatric syndromes such as vascular dementia, malnutrition, functional decline in Activities of Daily Living, mobility impairment and chronic ulcerous disease. Furthermore, there was a tight relationship between AF and Rockwoods' frailty phenotypes. This association was maintained throughout multivariable modelling including age (OR 1.06, IC 1.03–1.14, p = 0.042), sex (OR 2.30, IC 1.11–4.84, p = 0.026), congestive heart failure (OR 3.70, IC 1.77–7.91, p < 0.001) and a CFS more than 4 (OR 2.68, IC 1.18–6.43, p = 0.021). Conclusion: A deeper understanding of associations between atrial fibrillation and geriatric syndromes and frailty could give new patient management perspectives beyond pharmaceutical or interventional treatment.